2016
DOI: 10.1038/srep36982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Periplocoside P from Periploca sepium on the Midgut Transmembrane Potential of Mythimna separata Larvae

Abstract: Periplocoside P (PSP) isolated from the root bark of Periploca sepium contains a pregnane glycoside skeleton and possesses high insecticidal properties. Preliminary studies indicated that PSP disrupts epithelial functions in the midgut of lepidopteran larvae. In the present study, we examined the effects of PSP on the apical and basolateral membrane voltages, Va and Vbl, respectively, of cells from (1) midguts isolated from the larvae of the oriental armyworm Mythimna separata that were in vitro incubated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…We found that although the effects of CV on the V am of M. separata are less intense than those of Cry1Ab, the action on V am of the former is faster than that of the latter. Although a previous report showed that the V-ATPase of the insect midgut is a possible target of Bt toxins [ 31 ], we maintain that the influence of Cry1Ab on V am is mainly due to pore formation in the apical membrane [ 32 ]. The action mechanisms of Cry1Ab promote V am depolarization more effectively than those of CV, which may only target V-ATPase.…”
Section: Discussionmentioning
confidence: 63%
“…We found that although the effects of CV on the V am of M. separata are less intense than those of Cry1Ab, the action on V am of the former is faster than that of the latter. Although a previous report showed that the V-ATPase of the insect midgut is a possible target of Bt toxins [ 31 ], we maintain that the influence of Cry1Ab on V am is mainly due to pore formation in the apical membrane [ 32 ]. The action mechanisms of Cry1Ab promote V am depolarization more effectively than those of CV, which may only target V-ATPase.…”
Section: Discussionmentioning
confidence: 63%
“…PSP may first directly bind with the V-ATPase A subunit, thus affecting its catalytic ability to hydrolyze ATP, and eventually causing the overall dysfunction of the midgut system. Alternatively, PSP can directly affect apical membranes in M. separata midguts through transmembrane potential depolarization [ 46 ] and suppress V-ATPase activity in the malpighian tubules of Aedes aegypti [ 47 ]. These results are highly consistent with the results in this study, further confirming our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Through their in-depth research exploring new pesticides and their action mechanisms against insects, Hu’s group found that the apical and basolateral membrane voltage ( V a ) rapidly decreased in the presence of periplocoside P in a time- and dose-dependent manner, similar to the effects of Cry1Ab. They speculated that periplocoside P adjusted the transport mechanisms at the apical membrane of the midgut epithelial cells by inhibiting the V-type H + ATPase [194]. In addition, the V-type ATPase A subunit in the midgut epithelium might be regarded as the target binding site of periplocosides, which provided preliminary evidence for the mode of action of periplocosides [195].…”
Section: Biological Activitiesmentioning
confidence: 99%